2003
DOI: 10.1021/ja037947w
|View full text |Cite
|
Sign up to set email alerts
|

The SPR Sensor Detecting Cytosine−Cytosine Mismatches

Abstract: We have synthesized the first surface plasmon resonance (SPR) sensor that detects cytosine-cytosine (C[bond]C) mismatches in duplex DNA by immobilizing aminonaphthyridine dimer on the gold surface. The ligand consisting of two 2-aminonaphthyridine chromophores and an alkyl linker connecting them strongly stabilized the C[bond]C mismatches regardless of the flanking sequences. The fully matched duplexes were not stabilized at all under the same conditions. The C[bond]T, C[bond]A, and T[bond]T mismatches were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 108 publications
(72 citation statements)
references
References 36 publications
1
71
0
Order By: Relevance
“…Accordingly, we have used 8-azaquinolone as the recognition element for the adenine, 19,20 and protonated form of 2-amino-1,8-naphthyridine as the recognition element for the cytosine. 21 The mismatch binding ligands (MBLs) we have so far discovered are shown in Figure 5. In this article, we describe the inside story of MBLs about the discovery, identifying the function, and the application in genomic science.…”
Section: Conceptual Model For Mismatch Recognitionmentioning
confidence: 99%
See 3 more Smart Citations
“…Accordingly, we have used 8-azaquinolone as the recognition element for the adenine, 19,20 and protonated form of 2-amino-1,8-naphthyridine as the recognition element for the cytosine. 21 The mismatch binding ligands (MBLs) we have so far discovered are shown in Figure 5. In this article, we describe the inside story of MBLs about the discovery, identifying the function, and the application in genomic science.…”
Section: Conceptual Model For Mismatch Recognitionmentioning
confidence: 99%
“…After many trials for recognition elements, we eventually found that N-alkyl-2-amino-1,8-naphthyridine strongly and selectively bound to the cytosinecytosine mismatch. 21 The ligand we have developed for the recognition of the CC mismatch was the dimeric form of aminonaphthyridine (amND).…”
Section: Mismatch Recognitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the susceptibility of SPs to surrounding dielectric, SPs and surface plasmon resonance (SPR) exhibit excellent properties for sensing applications [11][12][13]. In past decades, various plasmonic sensors based on SPs and SPR have been proposed and investigated [14][15][16][17][18][19][20][21][22][23][24], especially prism-coupled SPR sensors [14][15][16][17] and fiber-coupled SPR sensors [20][21][22][23][24]. Generally, dimensions of prism-coupled SPR sensors are huge for integration of sensors on chips and their sensitivities are not high compared to fiber-coupled SPR sensor.…”
Section: Introductionmentioning
confidence: 99%